ISOLASI DAN IDENTIFIKASI ANTOSIANIN DARI HIBISCUS ROSA SINENSIS L DAN HIBISCUS SABDARIFFA L SERTA APLIKASI EKSTRAK DAN ANTOSIANINNYA SEBAGAI INDIKATOR DALAM TITRASI ASAM-BASA - , SITI NURYANTI; , Prof. Drs. Sabirin Matsjeh, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Synthetic acid-base indicators which have been used so far, posses several weaknesses, such as their limited availability and mostly are still imported. On the other hand, the demand for acid-base indicators for laboratory activities is increasing. Thus, the continuous efforts are needed to obtain the substances for the synthetic indicators which are urgently required. The research was aimed to isolate and identify the anthocyanin of Hibiscus rosa sinensis L and roselle (Hibiscus sabdariffa L) flowers as well as the application of their extracts and anthocyanins as indicators in acid-base titration. Isolation was initiated by extraction process using solvents which have different levels of polarity. n-Hexane were used to extract nonpolar compounds. This was followed by using of ethyl acetate to isolate semi polar compounds, while anthocyanins of Hibiscus rosa sinensis L flower were extracted by solvent mixture of methanol-HCl 1%. Anthocyanins of roselle flower were extracted by solvent mixture of methanol-HCl 0.5%. Both flower extracts were tested in acid-base titration, comparable to methyl orange and phenolphthalein indicators. The purification of anthocyanin from extracts of Hibiscus rosa sinensis L and roselle flowers was done by chromatography column technique with silica gel using of n-butanol:HCl 1% (4:1) and n-butanol:HCl 0.5%:etanol (5:1:4) as eluents. The identification of anthocyanin was conducted by using color reagents (ammonia vapor and solution of Pb acetate 1%). Structure identification was conducted by means of UV-Vis, FT-IR, 1 H- and 13 C-NMR spectrometries. From the identification, it was proved that Hibiscus rosa sinensis L and roselle flowers there are anthocyanins. Spectroscopy analyses showed that Hibiscus rosa sinensis L flower contained anthocyanin of pelargonidin while roselle had anthocyanin of cyanidin-3-glucoside. Application of Hibiscus rosa sinensis L and roselle extracts and anthocyanins as indicators in acid-base titration showed that the titration end point and pH trajectory were almost the same with methyl orange and phenolphtalein. The two pH ranges of Hibiscus rosa sinensis L and rosell extracts, were 3-5 and 8-10. The colors of Hibiscus rosa sinensis L and roselle indicators were red in acid solution and green in base condition. The anthocyanins of Hibiscus rosa sinensis L and rosell extracts are sensitive to light.